Communication in the age of the COVID-19 pandemic - MacNeil, Theresa, 1982- (Lexington Books, 2021)
Communication in the Age of the COVID-19 Pandemic centers around changes in communication as a byproduct of the COVID-19 pandemic. Specific contexts include changes in our intimate relationships and changes in how media outlets communicate to audiences.